Morphology of two cities from the Abbasid era Kufa and Samarra (Journal of the College of Basic Education, 2023)
The city's morphology is linked to physical and cultural aspects, and the first aspect representsA- The location of the city and the natural and physical characteristics.B- It represents the city plan.C- and the models of its buildings ().The civilizational history and heritage of Iraq is part of the Arab-Islamic history. The styles and methods of Arab architecture were reflected in the styles of the emergence of architecture in Iraq, and this important art flourished and developed, which represents a bright page from the pages of Arab architecture.The Arab Muslim leaders, including caliphs and kings, had an effective and important role in the emergence and continuity of the Arab city, so their great role came in decision-making, participation in planning and supervision of implementation, especially those that were characterized by the nature of public buildings such as university mosques, schools and the role of the emirate, and then comes the role of residents from workers, builders and carpenters. A sculptor, an engraver, and a calligrapher made these great works immortalize their makers and remain a trace that gives the Islamic civilization the characteristic of survival.The building and house layout is one of the struggles of civilization, which calls for luxury and ease, and that is late for Bedouinism and its doctrines (), and this research came to give a clear picture of a small part of an ancient civilization about two Iraqi cities. An Islamic civilization distinguished by its originality.The second is the city of Kufa, which grew up on the ruins of the city of Al-Hirah, flourished and developed, and continues to provide its services to this day.